KRIMINALITAS DAN MAKROEKONOMI DI ASEAN : APAKAH MEMILIKI HUBUNGAN KAUSALITAS? - Hasanah Hasanah (ABDI EQUATOR, 2023)
This study aims to determine and analyze the causal relationship between crime rates and macroconomic indicators in 5 ASEAN countries. The type of research used is quantitative and descriptive research where the data used are secondary data in the form of panel data from 2012 to 2018. The data analysis used is descriptive and inductive analysis. in the inductive analysis there are several, namely: (1) Unit Root Test (2) Cointegration Test. (3) Granger Causality Test The results of this study indicate that (1). there is no causal relationship between crime and income disparity, (2) Crime does not have a significant short-term causality relationship with poverty. Meanwhile, poverty has a significant long-term causality relationship with crime. (3)  There is no causal relationship between crime and unemployment. Based on the results of this study, the authors suggest that the government combines policies of income distribution, poverty, and unemployment, such as implementing progressive taxes and expanding employment, as well as tightening state security.